Off-Axis Polarization Volume Lens for Diffractive Waveguide - Lixuan Zhang; Yishi Weng; Ran Wei; Chuang Wang; Yuchen Gu; Chenyu Huang; Yuning Zhang (Crystals, 2023)
In augmented reality diffractive waveguide technology, the light field needs to be collimated before being transmitted into the diffractive waveguide. Conventional schemes usually require additional collimating optics to collimate the light from the micro-image source and guide it into the waveguide in-coupling elements. In order to meet the needs of head-mounted devices and further miniaturize the equipment, this paper proposes a waveguide device that combines collimation and coupling by using a reflective polarization volume lens (PVL). A related model is also established and simulated to calculate the diffraction and transmission characteristics of the PVL element, and is then improved to fit the experiment. The diffraction lens studied in this paper has high diffraction efficiency with a large off-axis angle, which can fold the optical path and reduce considerably the volume of the optical system when applied to the waveguide system.